Tinjauan Hukum Terhadap Penjualan Tanah Warisan Anak di Bawah Umur Kajian Putusan Nomor 154/Pdt.P/2022/PN Mlg - Susanto, Agung (UNIB Press, 2026)
This study discusses the legal review of the sale of inherited land by minors in Decision Number 154/Pdt.P/2022/PN Mlg. The purpose of this study is to analyze the judge's legal considerations when deciding the sale of inherited land by minors in case number 154/Pdt.P/2022/PN Mlg. This study uses a type of normative juridical legal research, namely research that focuses on examining the application of rules or norms in positive law collected through library research, by referring to documents or literature related to cases of the sale of inherited land by minors. This study uses a case approach and a statute approach. The results of the study show that the panel of judges in Decision Number 154/Pdt.P/2022/PN Mlg in their considerations have based the principle of the best interests of the child by using the literature of the book Guidelines for the Implementation of Duties and Administration of the Court in Four Judicial Environments Book II 2007 Edition printed in 2009, and Articles 1320, 1329 and 1330 of the Civil Code which allow Guardian Erna Widyawati to represent her children to sign the Deed of Sale and Purchase of property inherited from her husband.